Perfil imuno-histoquímico do infiltrado inflamatório no front de invasão em carcicomas epidermóides de língua e lábio inferior - Silveira, Ericka Janine Dantas da (2007)
The progression of the oral squamous cells carcinomas (OSCCs) seems to suffer influence from related factors to the host, as local and systemic immunologic response, which are essential to the antineoplasic defenses. The purpose of this study was evaluate the local immunity in 30 tongue and 20 lower lip SCC by immunohistochemistry method, utilizing antibodies anti-CD3, CD4, -CD8, -CD25 e -ζ(zeta), which immunoexpressions were compared considering the anatomical localization, the intensity of the inflammatory infiltrate into the front of invasion and metastases. The CD4/CD8+ ratio was calculated for each case and associate with the mentioned variable, being the intensity of the inflammatory infiltrated also compared with the anatomical localization and metastase and for this the cases had been grouped in two categories: (n = 10) absent/scarce inflammatory infiltrate; and (n = 40) moderate/intense infiltrate. Fisher´s exact test was performed (α= 0.05) and it was not observed any significant correlation between these groups with anatomical sites and metastases. With regard to the immunoexpression, the CD3+, CD4+, CD8+ and CD25+ cells count was higher in the lower lip SCCs while the anti-ζimmunomarcation was more evident in the non metastatic cases. Through the statistical analyses, it was verified that the CD3 exhibited positive-significant correlation with the inflammatory infiltrate (p = 0.023). Furthermore, antibodies against CD8 and CD25 cells were also significantly correlated with the inflammatory infiltrate (p = 0.002 and 0.030, respectively) and with the anatomical site (p = 0.004 and p = 0.004) mainly in the lower lip SCCs. CD4/CD8 ratio did not show significant association with metastase nor with anatomical localization. We conclude that the inflammatory infiltrated of the Bryne s (1998) system did not constitute an indicator of aggressiveness in the tongue and lower lip SCCs analyzed and that clinical behavior of the SCCs studied was related in part to the immunohistochemical profile of infiltrated the inflammatory present in tumoral invasion front